Flexible Organizational Structure and Typology of the Informal Small Entrepreneurship in Russia - Chepurenko, Alexander (Journal of Economic Sociology, 2019)
In this article, based on relevant domestic and foreign literature, the institutional (i.e., “narrower”) approach to the definition of informal entrepreneurship and the informal entrepreneurial activity are substantiated, and an analysis of their causes and practices in the conditions of modern Russia is delivered. Using data from the panel study of start-ups and small entrepreneurs conducted by the author (Moscow, 2013–2015), the paper addresses the following issues: (1) Are there any differences in the nature of ownership relations in those businesses that are partially or primarily informally led, from the classical property relations in entrepreneurial firms described in academic literature? (2) What are the types of SMEs, and why are those that use informal practices more common? (3) What role does interaction with State control and law enforcement bodies play in decision making of entrepreneurs as to whether to operate informally, and what are the possible alternatives? (4) What are the comparative advantages and risks/constraints of informal entrepreneurship? (5) Is there entrepreneurial motivation and the inclination for informal kinds of activity in the business and, if so, how? The main evidence of the article consists in the following: an important reason for the informality in micro and small businesses is a diffuse structure of property relations, which is a hybrid (mixed) form of a market and firm. An own typology of entrepreneurs is invented, based on various combinations of entrepreneurial motivation and levels of formalization of the latter. As a result, four ideal types of entrepreneurs are introduced, namely “stars,” “non-routine entrepreneurs,” “simpletons,” and “marginals.” The two latter are the main actors of the informal entrepreneurial activity of legally registered businesses and totally informal entrepreneurship, respectively. In conclusion, there are some practical recommendations formulated on opportunities to reduce informal entrepreneurial practices, based, among others, on the understanding of the differences between the aforementioned ideal types of entrepreneurs.